Drug Development Targeting the Glycogen Synthase Kinase-3β (GSK-3β)-Mediated Signal Transduction Pathway: Targeting the Wnt Pathway and Transplantation Therapy as Strategies for Retinal Repair - Fumitaka Osakada; Masayo Takahashi (Elsevier, 2009)
Recent advances in stem cell biology have provided new insights that may lead to the development of regeneration therapy in the central nervous system to replenish lost neurons and to reconstitute neural circuits. The strategies for regeneration can be classified into two approaches: i) activation of endogenous neural stem cells and ii) transplantation of donor cells to replace lost cells. In the adult mammalian retina, Müller glia generate new retinal neurons in response to injury. The proliferation and differentiation of Müller glia-derived progenitors can be controlled by both intrinsic and extrinsic factors. Members of the Wnt/β-catenin signaling pathway, such as Wnt receptors and glycogen synthase kinase-3β, may be promising drug targets for neural regeneration. On the other hand, transplantation of photoreceptors or retinal pigment epithelia derived from human embryonic stem cells or induced pluripotent stem cells is also promising. Directed differentiation of pluripotent cells into retinal cells and purification to obtain retinal cells at a specific ontogenetic stage are required for donor cell preparation. Modulation of the host retinal environment to reduce the glial barrier is also critical for transplantation. To restore visual function, we need to understand the mechanisms underlying the integration of newly generated neurons or transplanted cells into the existing neural networks. Keywords:: neurogenesis, rod and cone photoreceptor, eye, cell replacement, induced pluripotent stem (iPS) cell, glycogen synthase kinase-3β (GSK-3β)